2020
DOI: 10.1108/ijhcqa-01-2020-0009
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the Expanded Mindful Eating Scale

Abstract: PurposeTo develop and validate the Expanded Mindful Eating Scale (EMES), an expanded mindful eating model created for the promotion of health and sustainability.Design/methodology/approachA cross-sectional study using self-administered questionnaire surveys on Ochanomizu Health Study (OHS) was conducted. The survey was provided to 1,388 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 35 publications
0
16
0
1
Order By: Relevance
“…In our study, the original six-factor MES structure was not confirmed, and several items have been removed, as they negatively affected model fit indices. Our results suggest that more studies with MES are needed to confirm its structure, including testing correlations between MES and other scales used to measure ME [ 28 , 30 , 31 , 32 , 33 ] to ensure that MES is a reliable and valid tool to assess ME.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In our study, the original six-factor MES structure was not confirmed, and several items have been removed, as they negatively affected model fit indices. Our results suggest that more studies with MES are needed to confirm its structure, including testing correlations between MES and other scales used to measure ME [ 28 , 30 , 31 , 32 , 33 ] to ensure that MES is a reliable and valid tool to assess ME.…”
Section: Discussionmentioning
confidence: 91%
“…IES-2 incorporates an additional, fourth IE domain (“Body–Food Choice Congruence”), coherent with IE principles presented by the authors of this construct [ 8 ]. On the other hand, there are several measures to assess ME, for example, the Mindful Eating Questionnaire [ 28 ], the Mindful Eating Scale [ 29 ], the Expanded Mindful Eating Scale [ 30 ], the Mindful Eating Inventory [ 31 ], the Mindful Eating Behavior Scale [ 32 ], or the Four-Facet Mindful Eating Scale [ 33 ]. Nonetheless, to our knowledge, no adaptation study was conducted in the Polish representative population, which limits the possibility to use any of the mentioned instruments.…”
Section: Introductionmentioning
confidence: 99%
“…In the validity and reliability study of the expanded mindful eating scale, a negative correlation was found with the eating disorder inventory [22].…”
Section: Discussionmentioning
confidence: 99%
“…In light of these promising studies, it is very important to have reliable and valid tools to measure the change in which mindful eating interventions targeted. Therefore, mindful eating tools have been developed to assess conscious eating [19][20][21][22][23], and validity and reliability studies have been conducted in different sample groups [24][25][26]. The most cited and rst mindful eating tool in the literature was developed by Framson et al consists of a 28 items and 5 sub-scales (disinhibition, awareness, external cues, emotional response, and distraction) [20].…”
Section: Introductionmentioning
confidence: 99%
“…A higher total MEQ score indicates a higher level of mindful eating traits, which is found to be negatively associated with weight status in adults [ 4 ]. Although other measurements, such as the Expanded and Four-Facets Mindful Eating Scales or inventory are available for adults [ 5 , 6 , 7 ], the MEQ has been widely used as a primary mindful eating measurement in practice [ 7 ].…”
Section: Introductionmentioning
confidence: 99%